2022
DOI: 10.1001/jamanetworkopen.2021.41898
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel ω-3 Krill Oil Agent in Patients With Severe Hypertriglyceridemia

Abstract: IMPORTANCEIntense interest exists in novel ω-3 formulations with high bioavailability to reduce blood triglyceride (TG) levels. OBJECTIVE To determine the phase 3 efficacy and safety of a naturally derived krill oil with eicosapentaenoic acid and docosahexaenoic acid as both phospholipid esters (PLs) and free fatty acids (FFAs) (ω-3-PL/FFA [CaPre]), measured by fasting TG levels and other lipid parameters in severe hypertriglyceridemia. DESIGN, SETTING, AND PARTICIPANTS This study pooled the results of 2 ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
(50 reference statements)
0
10
0
1
Order By: Relevance
“…Interestingly, the serum apo-B content was not changed between the groups, suggesting that the quality of HDL and LDL might not be changed. More recently, the consumption of omega-3 krill oil (4 g/d) for 26 weeks resulted in a decrease in the TG, but no significant improvement in HDL-C [ 50 ]. Therefore, despite the conflicting data, it can be concluded that the consumption of omega-3 did not increase the serum HDL-C in both long-term and short-term consumptions.…”
Section: Change In Hdl-c Quantity During One’s Lifetimementioning
confidence: 99%
“…Interestingly, the serum apo-B content was not changed between the groups, suggesting that the quality of HDL and LDL might not be changed. More recently, the consumption of omega-3 krill oil (4 g/d) for 26 weeks resulted in a decrease in the TG, but no significant improvement in HDL-C [ 50 ]. Therefore, despite the conflicting data, it can be concluded that the consumption of omega-3 did not increase the serum HDL-C in both long-term and short-term consumptions.…”
Section: Change In Hdl-c Quantity During One’s Lifetimementioning
confidence: 99%
“…In 2004, Bunea et al demonstrated that administration of krill oil 1–3 g/day reduced the levels of total cholesterol, triglycerides, and LDL in patients with hypercholesterolemia, compared with levels produced by fish oil and a placebo [ 14 ]. Moreover, Parolini et al reported that dietary supplementation of krill oil reduced VLDL and IDL/LDL-cholesterol levels in apoE-deficient mice [ 15 ], and Mozaffarian et al found that a krill-oil-derived ω-3 formulation reduced TG levels in patients with severe hypertriglyceridemia [ 19 ]. Accordingly, we observed the factors involved in cholesterol synthesis in the liver to investigate the mechanism of the antihypercholesterolemic effects of krill oil.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of F-HTG focuses on the reduction of low-density lipoprotein (LDL) cholesterol levels, followed by management of non–high-density lipoprotein cholesterol levels; this can be achieved by changes in lifestyle and dietary modifications [ 126 ] or by the administration of statins such as Atorvastatin, Lovastatin, Fluvastatin, Pravastatin Rosuvastatin and Simvastatin [ 127 ]. Fibrates [ 128 ], Niacin [ 129 ] and Fish oil [ 126 , 130 , 131 ], The development of alternatives to statins, which include Evinacumab, the angiotensin-like 2 monoclonal antibody [ 132 ], which has shown adequate safety in trials [ 133 ]. The resurgence of approval for monoclonal antibody treatments for rare disorders [ 134 ] and gene therapy in animal models [ 135 ] will set the direction for the advancement of therapeutics for the management of this emerging disorder.…”
Section: Familial Hypertriglyceridemiamentioning
confidence: 99%